Compreensão sobre jogos e brincadeiras e o trabalho pedagógico das professoras de uma pré-escola pública de Manaus - Leão, Leticia Ramos Flores (Brasil, 2023)
Playing is essential for child development, because it stimulates autonomy, creativity, and reflexive abilities, acting on the child's physical, social, cultural, emotional, affective, and cognitive development. The study's objective is to understand the conceptions about games and play that guide the work of teachers of a public preschool in the south zone of Manaus. Regarding the data collection procedure, a semi-structured interview composed of 10 questions was conducted with 4 teachers. According to what was expressed by the teachers in the interviews, playing is valued as an important aspect of the practice, although it is understood from the perspective of didactic play, in the service of teaching content, which devalues playfulness, shows a conception of curriculum away from what the Brazilian legislation on early childhood education advocates and limits the development of the child.